Decoding the functional plasticity of milk-derived exosomes: implications for nutrition, immunity, and therapy - Hussain, Shahid; Ijaz, Sundas; Wajid, Abdul; Qadeer, Abdul; Suliman, Muath; Alzahrani, Fuad M.; Alzahrani, Khalid J.; Alsharif, Khalaf F.; Chang, Chieh-Wei; Chen, Chien-Chin (Frontiers in Immunology, 2025)
Through the targeted release of immunologically active cargo, milk-derived exosomes (MDEs) are becoming increasingly important channels for maternal-neonatal communication. This study summarizes available data, showing that the bioactivity of MDEs varies and is significantly influenced by factors such as species origin and lactation stage (colostrum versus mature milk). It is argued that this functional variability presents both opportunities and challenges for developing therapeutics and is crucial for understanding their role in shaping the newborn’s immune system. The composition of colostrum-derived MDEs differs significantly from that in mature milk, although both are rich in immunomodulatory microRNAs (such as miR-181a and miR-155) and proteins that promote immune tolerance and gut barrier integrity. Furthermore, the importance of careful source selection is highlighted by interspecies differences in MDE cargo, such as the varying anti-inflammatory properties of camel versus bovine exosomes. To address major challenges like standardization and scalable production, the potential of MDEs as natural nano-carriers for immunomodulatory therapy was critically evaluated. This review offers a framework for future research in nutritional immunology, moving beyond a simple component list to critically assess source-dependent functionality.